The difference between hypertension determined by self-report versus examination in the adult population of the USA: Continuous NHANES 1999–2016. (28th November 2019) - Delhey, Leanna; Shoults, Catherine; Johnson, Kemmian; Orloff, Mohammed; Faramawi, Mohammed F; Delongchamp, Robert
Abstract: Background: Studies have considered the validity of self-reported hypertension relative to hypertension detected by examination; no study has explored trends in the difference between these two measures. Our objective was to calculate these differences overtime within subpopulations of the USA. Methods: We included non-Hispanic white, non-Hispanic black and Hispanic adults who participated in the National Health and Nutrition Examination Surveys from 1999 to 2016, in the analysis ( N = 44 333). We subtracted self-reported hypertension from hypertension detected by examination to calculate blood pressure difference (BPD). We fit weighted linear regression models that included important covariates along with all combination of two- and three-way interactions to predict the BPD. We used the fitted lines of the models to depict the patterns of differences in the different subpopulations. Results: Age ≥ 45 years, lack of annual clinical visit, body mass index (BMI) < 25 and time were important factors associated with increased BPD. Conclusions: People who are ≥ 45 years, have normal BMI, or do not have annual medical visits are more likely to have a bigger BPD. We can use the calculated BPD, to adjust estimates of the prevalence of self-reported hypertension.